Role of Natural Antioxidant Products in Colorectal Cancer Disease: A Focus on a Natural Compound Derived from Prunus spinosa, Trigno Ecotype - Maria Condello; Stefania Meschini (Cells, 2021)
Colorectal cancer (CRC) is on the rise in industrialized countries, which is why it is important to find new compounds that are effective, with little or no adverse health effects. CRC arises from some cells of the epithelium which, following a series of genetic or epigenetic mutations, obtain a selective advantage. This work consists of a review on endogenous and exogenous antioxidant products that may have an efficacy in the treatment of CRC and an experimental study, in which the treatment was carried out with a natural compound with antitumor and antiproliferative activity, Prunus spinosa Trigno ecotype, patented by us, on HCT116 colorectal carcinoma cell line. The superoxide content was quantified after the treatments at different concentrations (2, 5, or 10 mg/mL) by means of the DHR123 probe; loss of the mitochondrial membrane potential with the tetramethylrodamine methyl ester (TMRM) cationic probe and reduced glutathione content (GSH) from monochlorobimane (MCB). This study revealed the importance of a careful choice of the concentration of the natural compound to be used in the CRC, due to the presence of a paradoxical effect, both antioxidant and pro-oxidant, depending on the different physiological conditions of the cell.